Interstitial cells of Cajal are functionally innervated by excitatory motor neurones in the murine intestine - Iino, Satoshi (Blackwell Science Inc, 2004)
Recent studies have demonstrated that intramuscular interstitial cells of Cajal (ICC) are preferential targets for neurotransmission in the stomach. Terminals of enteric motor neurones also form tight, synaptic-like contacts with ICC in the small intestine and colon, but little is known about the role of these cells in neurotransmission. ICC at the deep muscular plexus (ICC-DMP) of the small intestine express neurokinin 1 receptors (NK1R) and internalize these receptors in response to exogenous substance P. We used NK1R internalization as an assay of functional innervation of ICC-DMP in the murine small intestine. Under basal conditions NK1R-like immunoreactivity (NK1R-LI) was mainly observed in ICC-DMP (519 cells counted, 100% were positive) and myenteric neurones. ICC-DMP were closely apposed to substance P-containing nerve fibres. Of 338 ICC-DMP examined, 65% were closely associated with at least one substance P-positive nerve fibre, 32% were associated with at least two, 2% were associated with more than two nerve fibres and 1% with none. After electrical field stimulation (EFS, 10 Hz; 1 min) NK1R-LI was internalized in more than 80% of ICC-DMP, as compared to 10% of cells before EFS. Internalization of NK1R was not observed in myenteric ICC or smooth muscle cells in response to nerve stimulation. Internalization of NK1R-LI was blocked by the specific NK1 receptor antagonist WIN 62577 (1 μm) and by tetrodotoxin (0.3 μm), suggesting that internalization resulted from stimulation of receptors with neurally released neurokinins. These data suggest that ICC-DMP are primary targets for neurokinins released from enteric motor neurones in the intestine.